(untitled) (Journal on Excellence in College Teaching, 2024)
Effective instructional planning is paramount to successful learning experiences. Ideally, this commitment to success should be a shared effort by instructors and institutions. From providing faculty development programming to enhance pedagogical skills to examining the long-term impact of instruction, instructional readiness requires taking the long view in order to support the learning needs of teachers and their students. The authors in this issue of the Journal demonstrate the importance of planning for the success of instructors’ teaching and their students’ learning before, during, and after instruction.